2012
DOI: 10.1002/uog.11900
|View full text |Cite
|
Sign up to set email alerts
|

P09.24: Intrauterine treatment of a suprasellar inter‐hemispheric arachnoid cyst by feto‐cisternoscopy

Abstract: 22nd World Congress on Ultrasound in Obstetrics and GynecologyPoster abstracts acardiac twin was performed. Under fetoscopic observation, the cord was resected by scissors which inserted through operating channel in fetoscope. The patient delivered a 2290 g, female infant at 32 weeks of gestation after spontaneous rupture of membrane. Gross specimen of the placenta and acardiac twin showed complete obstruction of the anastomoses and no cord entanglement. P09.22Perinatal outcomes following radiofrequency ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Arachnoid cysts on the skull base showed more progression than those in other locations [19], with a 50% increase in the volume of suprasellar cysts during pregnancy [33]. Some reports have investigated experimental treatment using fetoscopy when the cyst size increases rapidly [33,44]. Chalouhi et al [44] reported that fetocisternoscopy with fenestration of the cystic wall cyst was successfully performed at 31 weeks in a fetus with a rapidly growing cyst.…”
Section: Antenatal Changes and Intrauterine Treatment Of Arachnoid Cystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachnoid cysts on the skull base showed more progression than those in other locations [19], with a 50% increase in the volume of suprasellar cysts during pregnancy [33]. Some reports have investigated experimental treatment using fetoscopy when the cyst size increases rapidly [33,44]. Chalouhi et al [44] reported that fetocisternoscopy with fenestration of the cystic wall cyst was successfully performed at 31 weeks in a fetus with a rapidly growing cyst.…”
Section: Antenatal Changes and Intrauterine Treatment Of Arachnoid Cystsmentioning
confidence: 99%
“…Some reports have investigated experimental treatment using fetoscopy when the cyst size increases rapidly [ 33 , 44 ]. Chalouhi et al [ 44 ] reported that fetocisternoscopy with fenestration of the cystic wall cyst was successfully performed at 31 weeks in a fetus with a rapidly growing cyst. The baby was born at 36 weeks of gestation, underwent an additional cisternoscopy after birth, and maintained good health after surgery.…”
Section: Antenatal Changes and Intrauterine Treatment Of Arachnoid Cystsmentioning
confidence: 99%